Genealogia da desigualdade: o impacto da branquitude escravocrata na região administrativa de Bauru - Nobrega, Ana Beatriz Rocha de [UNESP]; Vieira, Maria Eduarda [UNESP]; Moraes, Vanessa Pinto [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O “Genealogia da Desigualdade: o impacto da branquitude escravocrata na região administrativa de Bauru” é um livro-reportagem que visa expor a realidade do período escravocrata bauruense, bem como apontar seus impactos na sociedade atual, excepcionalmente quando se fala da relação entre pessoas brancas e negras. Por meio do jornalismo investigativo, obteve-se o produto final, que relata a história de famílias do centro-oeste paulista e personagens nacionais, apontando qual é a ligação desses indivíduos com a formação racista do Estado brasileiro.

"Genealogy of Inequality: the impact of slave whiteness in the administrative area of Bauru" is a report-book that aims to expose the reality of the Bauru slave period, as well as pointing out its impacts on today's society, especially when it comes to the relationship between white and black people. Through investigative journalism, the final product was obtained, which tells the story of families from the center-west of São Paulo and national characters, pointing out the connection between these individuals and the racist formation of the Brazilian system.
Genealogy of inequality: the impact of slave-owning whiteness in the administrative region of Bauru
Keywords: Jornalismo; Racismo; Ancestralidade; Bauru; Report-book; Journalism; Racism; Ancestry